MITIGASI, KESIAPSIAGAAN, DAN ADAPTASI MASYARAKAT TERHADAP BAHAYA KEKERINGAN, KABUPATEN GROBOGAN (Implementasi Sebagai Modul Konstektual Pembelajaran Geografi SMA Kelas X Pokok Bahasan Mitigasi Bencana) - Dwi Hastuti; Sarwono sarwono; Chatarina Muryani (GeoEco, 2017)
Mitigation, preparedness, and public adaptation for drought hazard in Grobogan regency(implementation as a contextual learning module of High School Geography Class X in the disastermitigation subject). Postgraduate thesis. Supervisor I: Dr. Sarwono, M.Pd, II: Prof. Dr. Chatarina Muryani,M.Si. Graduate Program in Population and Environmental Education. Sebelas Maret University Surakarta.The goals of this study are to determine: (1) public mitigation for drought hazard (2) public preparedness fordrought hazard (3) public adaptation for drought hazard in Grobogan regency (4) the implementation ofpublic mitigation, preparedness, and adaptation in Grobogan regency as supplement of contextual learningmodule on disaster mitigation material in class X Social Science Program.This research is descriptivequalitative. The subject of this research was the residents of Grobogan which experience drought and thegovernment (BPBD). The sample was collected using cluster random sampling technique.The sample for thisresearch was 120 respondens of 5 districts.The result of this research reveals: (1) drought mitigation inGrobogan resident is done by residents and government by constructing retention basins, creating drilledwells, building water tank, reforesting, and improving irrigation channels. The government also conductingsocialization of drought mitigation and implementing community sanitation program (Pamsimas) (2) publicpreparedness to face drought is done by residents by creating personal water tank, deepening their well, andpreparing reserve fund before the drought. The socialization of preparedness to face the drought is also doneby the government. (3) the adaptations which are done to face the drought are: cropping pattern adaptation,efficient water usage, provision of allocation of funds to purchase clean water from private, and maintaininghealth and providing medicine to face the disease due to drought. (4) the implementation in education, thisresearch is then implemented as contextual learning modules of mitigation and drought adaptation strategywhich is can be used in disaster mitigation material in class X second semester in 2013 curriculum. In thetried out of the module which is conducted for second semester students of class X SMA N 1 Wirosari,Grobogan regency. The responses given by a team of experts, geography teachers and the students weregood.Keywords: mitigation, preparedness, adaptation, implementation